Developing critical computer literacy for academic subjects 'English for Software Engineering' and 'Expert Systems' at the Department of Software Engineering University of Belgrade - Buric, M. D.; Draskovic, D. (2011 19th Telecommunications Forum, 2011)
Students at the Department of Software Engineering spend copious amounts of their time using computers both for studying by means of the Internet and for leisure. Having spent much time within the complex multimedia environment and being intimately familiar with software tools, our Software Engineering students meet new challenges in the form of critical computer literacy. In this paper we present the principles behind our decision to introduce critical computer literacy skills, their aims and the actual implementation in the domain of two academic subjects: English for Software Engineering and Expert Systems for students at the Department of Software Engineering.